Optimizing split fuel injection strategies to avoid pre-ignition and super-knock in turbocharged engines. (January 2021) - Singh, Eshan; Morganti, Kai; Dibble, Robert
Fuel injection strategies often have a considerable impact on pre-ignition in high specific output gasoline engines. Splitting the injection event into two or more pulses has been widely explored as one means of reducing pre-ignition. As effective as these strategies can be with respect to pre-ignition suppression, they often introduce other compromises into the combustion process, for example, reduced indicated mean effective pressure or greater cycle-to-cycle variation. This study examines a split injection strategy with up to three injection pulses for suppressing pre-ignition, while optimizing the start of injection and duration of injection to minimize the associated compromises on the combustion process. The results demonstrate that splitting the injection event generally lowers the in-cylinder temperature and reduces the fuel mass that reaches the cylinder liner. This leads to a lower probability of creating oil-fuel droplets, which may act as a precursor for pre-ignition. The split injection strategy with a late injection when the piston is close to top dead center is shown to perform even better in terms of pre-ignition suppression, while providing comparable indicated mean effective pressure and cycle-to-cycle variation to the baseline case with a single injection pulse. Finally, the injection pressure is varied to establish an optimal combination of operating parameters for avoiding pre-ignition in high specific output gasoline engines.